Acute Postexercise Change in Circulating Irisin Is Related to More Favorable Lipid Profile in Pregnant Women Attending a Structured Exercise Program and to Less Favorable Lipid Profile in Controls: An Experimental Study with Two Groups - Anna Szumilewicz; Aneta Worska; Magdalena Piernicka; Agnieszka Kuchta; Zbigniew Jastrzębski; Łukasz Radzimiński; Marta Kozłowska; Katarzyna Micielska; Ewa Ziemann (International Journal of Endocrinology)
Introduction. The blood irisin concentrations may be affected both by exercise and pregnancy. We aimed to determine acute responses in serum irisin after a single exercise session and relationships between exercise-induced changes in this hormone and lipid profile in pregnancy. Material and Methods. It was an experimental study in 20 Caucasian women in normal pregnancy (age 30±3 years, 28±6 weeks of gestation; mean±SD). Participants were assigned to training (n=8) and control groups (n=12). Before the experiment, women from the training group attended a structured exercise program 3 times a week for 6 weeks. Blood samples were collected before and 30 minutes after a single bout of 60-minute moderate- to high-intensity exercise to determine serum levels of irisin, insulin, glucose concentration, and lipid profile. Results. At baseline, we recorded slightly lower irisin levels in the training group compared to controls (12.2±2.4 and 13.9±3.3 ng·ml-1, respectively). Only in the training group all women presented increase in irisin levels after exercise (on average by 14%); and this change was statistically significant (p=0.002). In the controls, we found positive significant relationships between postexercise irisin change and low-density lipoproteins (R=0.594; p=0.04) and total cholesterol (R=0.734; p=0.006). Surprisingly, in the training group, these relationships were also significant but inverse (R=−0.738 and p=0.036; R=−0.833 and p=0.01, respectively). Conclusions. Training and control pregnant women responded differently to a single exercise session, both in the postexercise change in irisin and its relationship to the blood lipids. Only in the training group we observed the postexercise increase in irisin, which was related to more favorable lipid profile. Systematic prenatal physical activity may optimize the postexercise irisin response and lipid metabolism regulated by this hormone. Therefore, exercise programs should be promoted in pregnant women and obstetric care providers.